2022
DOI: 10.3389/fimmu.2022.814064
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and efficacy of ofatumumab and ocrelizumab in humanized CD20 mice following subcutaneous or intravenous administration

Abstract: Approval of B-cell-depleting therapies signifies an important advance in the treatment of multiple sclerosis (MS). However, it is unclear whether the administration route of anti-CD20 monoclonal antibodies (mAbs) alters tissue distribution patterns and subsequent downstream effects. This study aimed to investigate the distribution and efficacy of radiolabeled ofatumumab and ocrelizumab in humanized-CD20 (huCD20) transgenic mice following subcutaneous (SC) and intravenous (IV) administration. For distribution a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 50 publications
0
12
0
1
Order By: Relevance
“…Anti-CD20 antibodies are thought to penetrate lymphoid tissues more effectively than alemtuzumab, 3 but recent studies indicated persistence of B cells in lymphoid tissues following ocrelizumab or ofatumumab. 21 Although the peripheral CD19 + B-cell levels were not different in stable or relapsing patients having received FTY as last previous DMT, we were of course unable to evaluate whether this B-cell reservoir has been substantially altered. Generally, these compartment-specific effects might render development of durable biomarkers determined from peripheral blood difficult.…”
Section: Discussionmentioning
confidence: 80%
“…Anti-CD20 antibodies are thought to penetrate lymphoid tissues more effectively than alemtuzumab, 3 but recent studies indicated persistence of B cells in lymphoid tissues following ocrelizumab or ofatumumab. 21 Although the peripheral CD19 + B-cell levels were not different in stable or relapsing patients having received FTY as last previous DMT, we were of course unable to evaluate whether this B-cell reservoir has been substantially altered. Generally, these compartment-specific effects might render development of durable biomarkers determined from peripheral blood difficult.…”
Section: Discussionmentioning
confidence: 80%
“…In the Phase 3 ASCLEPIOS trials [ 9 ], ofatumumab was administered in a pre-filled syringe; however, ofatumumab is approved in Europe [ 14 ] as a pre-filled syringe and an autoinjector pen. Injection tolerability and patient satisfaction due to convenience of administration is improved with autoinjectors versus manual injection, thereby increasing adherence [ 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ofatumumab’s greater CDC than rituximab, ocrelizumab and ublituximab [ 66 , 67 , 71 , 73 , 74 ] is thought to mediate its greater efficacy at lower doses and suitability for subcutaneous administration compared with rituximab, ocrelizumab and ublituximab [ 67 , 68 ]. Furthermore, although CDC is ofatumumab’s primary mechanism of action, ofatumumab has also been shown to induce twofold higher ADCC than rituximab, with levels similar to ocrelizumab and reduced compared with ublituximab (Table 1 ) [ 41 , 75 , 76 ].…”
Section: Mechanism Of Action and Route Of Administrationmentioning
confidence: 99%
“…The majority of anti-CD20 mAbs for MS are administered via intravenous infusion, with the subcutaneous injection of ofatumumab being the exception. Studies have shown that these different routes of administration have biological and clinical consequences for the treatment of B cell-associated disease, including MS. For instance, subcutaneous administration of anti-CD20 therapies in mice has been shown to result in similar levels of depletion of circulating and lymph-node-localized CD20+ B cells when administered at a low dose, compared with the high-dose intravenous administrations [ 76 ]. Furthermore, low-dose subcutaneous administration is clinically associated with reduced administration-related reactions [ 41 ].…”
Section: Mechanism Of Action and Route Of Administrationmentioning
confidence: 99%
See 1 more Smart Citation